2014
DOI: 10.1186/s12909-014-0269-y
|View full text |Cite
|
Sign up to set email alerts
|

Students’ perspectives on research and assessment of a model template designed to guide beginners in research in a medical school in Cameroon

Abstract: BackgroundResearch activities for medical students and residents (trainees) are expected to serve as a foundation for the acquisition of basic research skills. Some medical schools therefore recommend research work as partial requirement for certification. However medical trainees have many difficulties concerning research, for which reason potential remedial strategies need to be constantly developed and tested. The views of medical trainees are assessed followed by their use and appraisal of a novel “self-he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 11 publications
(11 reference statements)
1
2
0
Order By: Relevance
“…Consistent with a Croatian study, the students’ attitude towards scientific practice is positive overall [19]. International studies also indicate results consistent with our own, in that students think they are poorly prepared for scientific research [5], or misjudge their competencies [20]. Medical educators worldwide are establishing new teaching concepts and methodologies in order to motivate students for research [21–24].…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Consistent with a Croatian study, the students’ attitude towards scientific practice is positive overall [19]. International studies also indicate results consistent with our own, in that students think they are poorly prepared for scientific research [5], or misjudge their competencies [20]. Medical educators worldwide are establishing new teaching concepts and methodologies in order to motivate students for research [21–24].…”
Section: Discussionsupporting
confidence: 74%
“…Several international publications suggest that medical students are very critical of their own abilities regarding almost all aspects of science [5, 6]. The participation of medical students in scientific research is hampered by a lack of motivation mostly resulting from inadequate access to scientific training programs and supervision [79].…”
Section: Introductionmentioning
confidence: 99%
“…These deficits are obviously not adequately addressed by the supervisors. Investigations of other curricular concepts aimed at developing scientific competencies have shown that students often feel insufficiently trained in the areas of practical methods, statistics and literature research, as well as the critical analysis of research results [31], [32], [33]. This judgement is supported by graduate survey data recently published by Epstein et al This finding revealed that these skills were not acquired until students were pursuing doctoral studies.…”
Section: Discussionmentioning
confidence: 95%